TEACHER QUESTIONING STRATEGIES IN ENGLISH CLASSROOM INTERACTION AT THE EIGHT GRADE STUDENTS OF SMK.SPP.ST. PAULUS MAKALE - matius tandi kombong (UKI TORAJA, 2017)
in English classroom interaction the eighth grade students of SMK.SPP. ST. PaulusMakale academic year 2016/2017.This research used a qualitative descriptive analysis method research. Theresearcher took sample in this research by using snowball sampling. It used to findout questioning strategies by the teacher in English classroom interactionat theeight grade students of SMK.SPP. ST. Paulus Makale academic year 2016/2017.The result of this research after analyzing the data it indicated that teacherquestioning strategies in English classroom interaction in the eight grade studentof SMK. SPP. ST. Paulus Makale showed that there are five kinds of questioningstrategies teacher used. They are (1) cold call, (2) not opt out, (3) think or inkpair-share, (4) go-around, (5) fist-to-five or thumb-ometer.